Psychometric properties of the Barratt Impulsiveness Scale version 11 among a Portuguese sample of incarcerated juvenile offenders - Pechorro, Pedro Fernandes dos Santos (2015)
The aim of the present study was to examine the psychometric properties of the Barratt Impulsiveness Scale version 11 (BIS-11) among a forensic sample of incarcerated male juvenile offenders (N = 221). Principal Component Analysis with Promax rotation revealed the expected 6-factor structure, but Confirmatory Factor Analysis of the 6-factor first-order and the 3-factor second-order factorial structures did not present sufficiently good fits. Despite that, the Portuguese adaptation of the BIS-11 demonstrated generally acceptable psychometric properties in terms of internal consistency, mean inter-item correlation, convergent validity, discriminant validity, and concurrent validity that justifies its use among the youth forensic population. Statistically significant associations were found with age of crime onset, conduct disorder, crime seriousness, alcohol use and drug use.